Stress test reflections on financial crises - Geithner, Timothy F (New York Crown Publishers, 2014)
From the former Treasury Secretary, the definitive account of the unprecedented effort to save the U.S. economy from collapse in the wake of the worst global financial crisis since the Great Depression
Award-winning business reporter Charles Duhigg takes us to the thrilling edge of scientific discoveries that explain why habits exist and how they can be changed. With penetrating intelligence and an ability to distill vast amounts of information into engrossing narratives, Duhigg brings to life a whole new understanding of human nature and its potential for transformation
The bombs -- An American abroad -- An education in crisis -- Leaning against the wind -- Letting it burn -- The fall -- "We're going to fix this" -- Into the fire -- Plan beats no plan -- Getting better, feeling worse -- The fight for reform -- Aftershocks -- Reflections on financial crises
Includes bibliographical references (pages [545]-558) and index
Keywords: Geithner, Timothy F; Global Financial Crisis, 2008-2009.; Financial crises|zUnited States|xHistory.; Banks and banking|zUnited States; Electronic books